Measuring bar pattern speeds from single simulation snapshots - Dehnen, Walter; Semczuk, Marcin; Schönrich, Ralph (Monthly notices of the Royal Astronomical Society, 2023)
We describe methods to measure simultaneously the orientation angle ψ and pattern speed Ω from single snapshots of simulated barred galaxies. Unlike previous attempts, our approach is unbiased, precise, and consistent in the sense that ψ = ∫ dt. It can be extended to obtain the rate and axis of rotation, i.e. the vector Ω. We provide computer code implementing our method.